First Detection of Listeria monocytogenes in a Buffalo Aborted Foetus in Campania Region (Southern Italy) - Esposito, Claudia; Cardillo, Lorena; Borriello, Giorgia; Ascione, Grazia; Valvini, Ornella; Galiero, Giorgio; Fusco, Giovanna (Frontiers in Veterinary Science, 2021)
Listeria monocytogenes (LM) is the causative agent of listeriosis in both animals and humans, representing one of the most severe food-borne diseases in humans. Out of 13 serotypes, only three (i.e., 1/2a, 1/2b, and 4b) are responsible for 95% of human outbreaks of listeriosis. Ruminants have been hypothesised to represent the main natural reservoir for this pathogen and to be involved in the transmission of Listeria to humans. During pregnancy, listeriosis in ruminants cause various reproductive disorders as well as abortion. However, little is known about abortion due to LM in water buffaloes (Bubalus bubalis). In this study, we report for the first time the detection of LM in a water buffalo foetus in the region of Campania, Italy. Complete necropsy was performed, and samples and swabs from the abomasum, kidneys, liver, lungs, and spleen were collected. Microbiological and molecular analyses were carried out to detect bacterial, viral, and protozoarian abortive pathogens. The results revealed the presence of LM in the liver, lungs, and abomasum, and no other agent was detected. Isolation was confirmed by biochemical and molecular tests. Molecular serotype characterisation was performed, and serogroup IVb was identified. In conclusion, because of the zoonotic implications of our findings, this report highlights the importance of including LM in the diagnostic panel in cases of bubaline abortion.